(untitled) (Research, Society and Development, 2021)
Dysphagia is characterized by a dysfunction in the swallowing process, which impairs safe and autonomous oral feeding. To minimize the negative effects, modified texture foods and thickened drinks are used. This study aimed to compare the viscosities of commercial food thickeners when dissolved in liquid preparations. Three starch-based thickeners were used to thicken five preparations (water, orange juice, milk, thickened milk, and coffee). Nutritional information, microscopy, pH, swelling power, and solubility of the granules and the viscosity of the preparations as a function of time and temperature were evaluated. All thickeners had a high percentage of carbohydrates, sodium, and the presence of modified starch. The thickeners promoted changes in the pH of the preparations and the presence of modified corn starch showed an increase in solubility and swelling power. About temperature variations, lower values ​​increased viscosity, and viscosity increased with rest, probably due to the continuous hydration of the thickening agent. The greater the consistency you want to achieve, the greater quantities of product need to be added. The thickened food preparations showed different viscosities, depending on the food matrix, temperature, time and the amount of product added.